CONSTRUCTION OF MEANING OF TRANSFER PRICING IN THE STAKEHOLDER THEORY THROUGH THE RICOEUR HERMENEUTICAL APPROACH - Utari, Dewi; Ludigdo, Unti; Achsin, M; Subekti, Imam (Accounting Department,, 2019)
This study seeks to find the meaning of transfer pricing of tax actors, namely Taxpayers and tax authorities, as well as tax consultants on tax disputes in Indonesia. The study was conducted using an interpretive approach and Ricoeur hermeneutical methods. Ricoeur's hermenutics method is carried out through three stages of analysis, namely the semantic stage, the reflection stage, and the existential stage. Analysis was carried out on the text, both written and unwritten. The written text is in the form of tax regulations related to transfer pricing, while the unwritten text is a dialogue in the transfer pricing dispute trial in the tax court and the results of interviews with taxpayers and tax consultants. Based on the three stages of Ricoeur hermeneutical analysis, the meaning of transfer pricing was obtained from three perspectives, namely the Taxpayer's perspective that interpreted transfer pricing as an effort to maximize company profits, whereas from the tax authority perspective transfer pricing was a potential loss of state revenue. In addition, the meaning of transfer pricing was also found from the perspective of a tax consultant as a form of the company's business strategy. The meaning of transfer pricing is then constructed in a stakeholder theoretical framework. Keywords: transfer pricing, hermeneutics, Ricoeur, company profits, state revenues, tax avoidance, and stakeholders.